Life history of oysters influences Vibrio parahaemolyticus accumulation in Pacific oysters ( Crassostrea gigas ) - Sorée, Marion; Delavat, François; Lambert, Christophe; Lozach, Solen; Papin, Mathias; Petton, Bruno; Passerini, Delphine; Dégremont, Lionel; Hervio Heath, Dominique (Environmental Microbiology, 2022)
Vibrio parahaemolyticus infection in humans is associated with raw oyster consumption. Evaluation of V . parahaemolyticus presence in oysters is of most interest because of the economic and public health issues that it represents. To explore V . parahaemolyticus accumulation and depuration in adult Crassostrea gigas , we developed a GFP‐tagged V . parahaemolyticus strain (IFVp201‐ gfp + ), as well as a rapid and efficient quantification method in C . gigas oysters haemolymph by flow cytometry. Impact of the life history of C . gigas on accumulation and depuration of V . parahaemolyticus IFVp201 was subsequently investigated. We found that naive oysters, i.e. grown in controlled facilities with UV treated seawater, accumulated significantly more IFVp201 than environmental oysters, i.e. grown in intertidal environment. We hypothesized that environmental oysters could have been immune primed, thus could limit V . parahaemolyticus accumulation. Meanwhile, both naive and environmental oysters had similar depuration rates.